ESTUDOS AFRICANOS NA FORMAÇÃO DE PROFESSORAS DO ENSINO MÉDIO DE UMA ESCOLA PÚBLICA EM IMPERATRIZ DO MARANHÃO - SANTOS, Eliana Rosa de Oliveira (2025)
This paper presents African Studies in the Training of High School Teachers at a School in Imperatriz do Maranhão, driven by the epistemological curiosity of knowing the place of Africa in the High School Teacher Training of Imperatriz, I identify as a problem the valorization of knowledge coming from Europe and the USA, to the detriment of knowledge from Africa, as a consequence of this, we analyze that the Brazilian social formation, built under the episteme of European knowledge, favored the historical and cultural erasure of Africa and its native peoples. However, we list the following questions: what is the place of African Studies in Teacher Training? And how do African Studies contribute to the training for ethnic-racial relations in schools? Thus, we elaborated three Objectives, (i) to understand how Eurocentrism contributed to the absence of EE and influenced the (de)formation of Brazilian racial relations; (ii) to investigate the impacts of the absence of EA in the training of high school teachers in Imperatriz do Maranhão; (iii) to analyze the paths that EA reveal for plural and anti-racist teacher training. In the theoretical foundation, we seek to understand the formative processes on the social identity construction of a Brazil that still lives under the coloniality of power and social classification (Quijano, 2010), (Memmi, 2007; Césaire, 1978). Moving away from the dominant epistemology (Global North), we appropriate epistemological alternatives such as the Epistemology of the South (Meneses; Santos, 2010) and Decolonial Thought (Mignolo, 2005; Quijano, 2005; Walsh, 2008). It is essential to include in this dialogue the categories, African Studies (Hountondji, 2010), decolonization of minds in the thought of Paulo Freire and Amílcar Cabral analyzed by Gadotti (2012), Coloniality of power (structure of power – knowledge and subjectivity) (Quijano, 2010), the Myth of Racial Democracy in Nogueira (1998), and necropolitics (Mbembe, 2018). In the Methodology we used Autobiographical Research in Education (Passeggi, 2016), the Culture Circle (Freire, 1987) and Discourse Analysis (Orlandi, 1999). And finally, the results achieved, knowledge of the Freirean Culture Circle and Autobiographical Research to identify the place(s) of an Africa dictated by the Eurocentric vision in the Brazilian Curriculum; inclusion of African Studies in Teacher Training, through the teachers’ autobiographical narratives; appropriation of African Studies to comply with Laws 10.639/03 and 11.645/08 and the construction of the Educational Product of African Studies in Teacher Training. Furthermore, strengthening anti-racist praxis against the processes of African invisibilization in training spaces.